Re-examining gender earning differentials in Malaysian manufacturing - Cheong, Jia Qi; Suresh Narayanan; Jacqueline Lisa Fernandez (MIT Press, 2022)
The manufacturing sector is a major avenue for female employment in the urban labor market in Malaysia. Only two studies, both published more than two decades ago, have examined gender earning differentials in this sector. Since then, the percentage of women being educated has increased, along with their participation rate, and several laws protecting their rights have also been passed, making it timely to re-examine the earnings gap. We do this by drawing on more recent data from a larger representative survey of manufacturing employees. The Blinder-Oaxaca technique, utilized in the previous two studies, was used to estimate the existing earnings gap and to decompose it to differences attributable to endowments, coefficients (traditionally viewed as subsuming discrimination), and the interaction between the two. We found a smaller gap than previously reported, with better female endowments helping to narrow the gap, and unexplained differences in coefficients being responsible for the remaining gap. The interaction effect was not statistically significant. Contrary to the earlier studies, the differential treatment of women in the manufacturing sector, rather than endowment differences, is hampering the equalization of earnings. This calls for newer approaches to closing the earnings gap.